Round reduction-based fault attack on SM4 algorithm - Min WANG; Zhen WU; Jin-tao RAO; Hang LING (Tongxin xuebao)
A novel method of fault attack based on round reduction against SM4 algorithm was proposed.Faults were in-jected into the last four rounds of the SM4 encryption algorithm,so that the number of the algorithm's rounds can be re-duced.In known-ciphertext scenario,four traces are enough to recover the total 128 bit master key by screening these faults easily.The proposed attack is made to an unprotected SM4 smart card.Experiment shows that this attack method is efficient,and which not only simplifies the existing differential fault attack,but also improves the feasibility of the attack.